Investigation of dry sliding wear and mechanical properties of hybrid epoxy composites reinforced with pineapple leaf and roselle fibers - K. Giridharan; B. Elumalai; M. Vinothkumar; G. Chakravarthi; D. Manikandan; Krishnaraj Ramaswamy (Scientific Reports, 2025)
Abstract Natural fiber composites have gained significant potential in past decades due to their favorable physical properties and mechanical characteristics. Pineapple leaf fibers and roselle fibers are abundant agricultural wastes and tend to be recycled to minimize environmental pollution. The present work aims to investigate and analyze the effects of reinforcing pineapple leaf fiber (PALF) and roselle fiber with epoxy hybrid composites. The composites are fabricated using the hot compression molding process. The mechanical attributes of the composites are studied through tensile, flexural, and impact tests. Along with a hybrid combination of fibers, a neat resin sample and samples of PALF and roselle fiber alone were also fabricated for test comparison. The wear behaviour of the fabricated specimen was explored by pin-on-disc wear test and examined the specific wear rate and co-efficient of friction properties. The fractographic studies of the hybrid composite fractured specimen through tensile and impact tests and the worn surface from the wear tests were analyzed using a scanning electron microscope. The results discovered that 25 wt% of PALF with 25 wt% of roselle fiber composite showed significant improvements in tensile characteristics, flexural and impact strength of 42.03 MPa, 38.17 MPa, and 46 KJ/m2. The best wear resistance was observed for 30 wt% PALF with 20 wt% of roselle fiber hybrid composite. Based on the experiments, hybrid fiber composite sample getting better wear and mechanical properties and suggesting their suitability to applications for cabinets like wardrobes, cupboards, and storage shelves.